Using the SAVI Model through Video and Peabody Media in Learning Arabic Speaking Skills - Hasyim, Mochamad; Wijaya, Mu'alim; Iliah, Mufidatul (Arabiyatuna: Jurnal Bahasa Arab, 2023)
The purposes of this study were to find out how Arabic speaking skills were taught at MTs. Darut Taqwa 02 Sengonagung Purwosari by applying the SAVI-based learning model, and to determine the effect of students' learning outcomes after the application of the SAVI model and to find out whether there were differences between the SAVI and conventional learning models on the learning outcomes of Arabic speaking skills. This study used a quantitative approach, with a quasi-experimental research design with a non-equivalent control group. The subjects were the students of class VII I, consisting of 35 students as the experimental class, and class VII K, comprising 37 students as the control class. Several tests were conducted, including a descriptive test, normality test, paired sample t-tests, homogeneity test, and independent sample t-test. The results obtained through several tests showed an increase in the average score between the pre-test (47.49) and post-test (67.97). Additionally, a comparison of the average post-test scores between the experimental class (67.97) and the control class (59.51) showed a difference of 8%. The conclusion is that the SAVI model using video and Peabody media for learning Arabic speaking skills is more influential than the conventional model.